The forests of Robinson Crusoe Island, Chile: an endemism hotspot in danger - Vargas, Rodrigo; Reif, Albert; Faúndez, María Jose (BOSQUE, 2017)
Robinson Crusoe Island (RCI), part of Juan Fernández Archipelago, contains more endemic plant species per area than any other island system of the world (1.9 species/km²). Currently, exotic plants are invading all habitats on the island with higher or lower intensity. As two-thirds of the vascular plant species are threatened by extinction, the island has a high conservation priority. Protection of the island’s biodiversity is of utmost importance both locally and globally. Using already published information, the main vegetation types defined for RCI were reviewed, considering plant species richness on the International Union for Conservation of Nature conservation categories, amount of invasive exotic plants, and the occurrence of land bird species. The highest number of endemic and endangered plant species was found in the upper and lower montane forest, in which only highly threatened and threatened bird species live. Furthermore, the scientific literature about Juan Fernández Archipelago was reviewed in order to identify missing data needed for effective conservational efforts. So far research in Juan Fernández and RCI has been mainly focused on Botany, usually dealing with taxonomical aspects of singular plant taxa. Detailed studies of ecology, structure, dynamics, processes and services of the forests on RCI are missing in scientific literature. It appears as highly important to fill this knowledge gap in order to be successful in future conservation and restoration initiatives.